Predictive factors for successful decannulation of the Montgomery T-tube in patients with complex airway stenosis during the COVID-19 pandemic at a tertiary hospital in Lima, Peru - Taipe Mallqui, Ricardo; Ampuero Porcel, Pamela; Perez Cuello, Monica; Palacios León, José (Current Challenges in Thoracic Surgery, 2026)
The Montgomery T-tube (MTT) is widely utilized for the management of complex airway stenosis; however, there is a lack of standardized clinical criteria and predictive models to determine the optimal timing for successful decannulation. This study aims to identify clinical and anatomical predictive factors for successful decannulation (SDMTT) in patients with complex airway stenosis during the coronavirus disease 2019 (COVID-19) pandemic.